Individual Inhalation Exposure to Phthalates and Their Associations with Anthropometric and Physiological Indices in Primary School Children in Jinan, China - Haoming Yang; Lixin Wang; Yuchen Wang; Ziyan Meng; Qinghua Sun; Jianlong Fang; Yu Zhong; Zihao Huang (Buildings)
Phthalates are commonly found in indoor environments. Consequently, children may be exposed to phthalates through the air, potentially causing health issues. We collected 72 air samples from 60 households and 12 classrooms in Jinan, surveyed and health-examined children, assessed their phthalate inhalation exposure, and analyzed the associations between inhalation exposure levels and children’s anthropometric and physiological indicators. Eight phthalates were detected in children’s households and classrooms, with detection frequencies ranging from 91.6% to 100%. Di-iso-butyl phthalate (DiBP), di-n-butyl phthalate (DnBP), and di (2-ethylhexyl) phthalate (DEHP) were the predominant phthalates. Children’s indoor inhalation exposure to phthalates ranged from 8.90 to 147 ng/(kg·day), with DEHP being the main inhaled phthalate. The non-carcinogenic risks of indoor environments where children live are within acceptable limits. DEHP has a low carcinogenic risk. Di-n-octyl phthalate (DnOP) exposure was associated with a decrease in body mass index z-score, waist circumference, and hip circumference. Additionally, DEHP exposure was negatively associated with the waist-to-hip ratio. DiBP exposure was negatively associated with the systolic blood pressure z-score, while DnOP exposure was negatively associated with the diastolic blood pressure z-score. Furthermore, DEHP exposure was positively associated with fractional exhaled nitric oxide z-score. The findings of this study suggest that phthalate inhalation exposure may substantially affect various health metrics in children, including body mass index, waist and hip circumference, and blood pressure, and increase the risk of respiratory tract inflammation.